Implications of Prenatal Healthcare Services Utilization on under-five Fever Occurrence in Cameroon - Adze, Romanus Ndam; Njoupouognigni, Moussa; Ningaye, Paul (Journal of Medicine, Nursing & Public Health, 2026)
This study provides a comprehensive analysis of the implications of prenatal healthcare service utilization on under-five fever occurrence in Cameroon. The main objective is to examine how prenatal healthcare service utilization correlates with the occurrence of fever among children under-five in Cameroon. Methodologically, the study used data from the Cameroon Demographic and Health Surveys (DHS) for the years 2011 and 2018, respectively. A logit model was employed to analyse the results. The findings reveal that Prenatal Healthcare Service Utilization (PHSU) is strongly correlated with under-five fever occurrence in Cameroon. In terms of policy, the study suggests that policymakers must pay careful attention to the types of prenatal care services utilized, as this has a direct implication on under-five fever occurrence outcome in Cameroon. Keywords: Prenatal Healthcare, Under-five fever occurrence, Logit model, Cameroon.